2021
DOI: 10.1002/ajs4.186
|View full text |Cite
|
Sign up to set email alerts
|

Universal child health and early education service use from birth through Kindergarten and developmental vulnerability in the Preparatory Year (age 5 years) in Tasmania, Australia

Abstract: This study investigated patterns of universal health and education service use from birth through Kindergarten (age 4 years) and estimated associations between cu- | 293TAYLOR eT AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Similarly, it is possible that certain combinations of risk factors could disproportionally contribute to the burden of ID. This knowledge could be used to develop risk indices which can be applied on a population level to identify the most vulnerable sectors of the community, 10.3389/fpsyt.2022.926681 where there will be the most gain from early intervention but where there is the highest risk of non-participation in universal developmental surveillance (22,23). The concept of proportionate universalism (24) provides a framework where universal services, both antenatally and into infancy, can be supplemented with additional services directed at those at highest risk.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it is possible that certain combinations of risk factors could disproportionally contribute to the burden of ID. This knowledge could be used to develop risk indices which can be applied on a population level to identify the most vulnerable sectors of the community, 10.3389/fpsyt.2022.926681 where there will be the most gain from early intervention but where there is the highest risk of non-participation in universal developmental surveillance (22,23). The concept of proportionate universalism (24) provides a framework where universal services, both antenatally and into infancy, can be supplemented with additional services directed at those at highest risk.…”
Section: Introductionmentioning
confidence: 99%
“…In total, six studies have examined the extent to which ECEC attendance (Chen et al, 2014; Guthridge et al, 2016; Short et al, 2019), dosage (Petriwskyj et al, 2014; Taylor et al, 2021) and quality (Gialamas et al, 2015; Petriwskyj et al, 2014) are associated with the risk of starting school already behind. Overall, studies found that both dosage and quality were important.…”
Section: Resultsmentioning
confidence: 99%
“…More evidence is needed on how adolescent health outcomes are shaped by other domains of child development, particularly the impact of language and communication, and cognitive and physical development at school starting age. Evidence on these domains are important for engaging health and education sectors to work together because education and health services share a common goal for optimal developmental potential of children [ 78 ]. This evidence would help the development of a shared understanding and provide a platform from which to develop the context and settings that may work best for optimal health and development of children, regardless of their stage of development when starting school.…”
Section: Discussionmentioning
confidence: 99%